PENGARUH KEMISKINAN DAN PENGANGGURAN TERHADAP KRIMINALITAS DI INDONESIA DI TAHUN 2019 - Kamal Fachrurrozi; Fahmiwati Fahmiwati; Lukmanul Hakim; Aswadi Aswadi; Lidiana Lidiana (Jurnal Real Riset, 2021)
This study aims to examine the effect of poverty and unemployment on crime in Indonesia. The research data used 34 provinces (cross-section) in 2019. The method of analysis used is multiple linear regression models with OLS estimation techniques. The results of this study found that poverty has a positive and significant effect on crime. Crime can increase by 0.32 percent if poverty increases by 1 percent. Meanwhile, unemployment has a positive and significant effect on poverty. If unemployment increases by 1 percent, crime will increase by 0.36 percent. This research recommends that the government pays more attention to the poor, especially in policies that are more supportive and reduce poverty. Meanwhile, in the case of unemployment, the government needs to open more jobs so that crime will be reduced.Keywords: Poverty, Unemployment, Crime, OLS.